Experiencing Provence in the regional imagery of Peter Mayle and Pierre Magnan - Briwa, Robert Merrill (Kansas State University, 2015)
Place-defining novelists convey regional imagery and regional sense of place to a wide audience, thus shaping popular perceptions of regions. Peter Mayle and Pierre Magnan are the most recent place-defining novelists of Provence, France. This research compares each author’s regional imagery and sense of place to understand what it means for each author to be in Provence. Place-name mapping geographically frames each authors’ regional imagery and sense of place. Qualitative coding and close readings of selected texts for each author identify sets of regional imagery, including nature and culture imagery, which help develop a sense of place for Provence. The subjectivities of qualitative coding analysis is addressed through personal narratives which acknowledges the researcher’s positionality vis-à-vis Provence. Mayle’s nature imagery emphasizes remote, rough topography and bright sunny skies, which presents the natural landscape as benevolent and therapeutic. Magnan’s nature imagery emphasizes rough topography, rivers, winds, and storms, which presents the natural landscape as powerful, indifferent or malevolent towards human affairs, and imbued with a sense of deep time and an enigmatic quality. Mayle’s culture imagery emphasizes healthy, traditional agrarian lifeways; vibrant village life and social connectedness; a positive and prominent tourist industry; and a food culture which permeates Provençal identity. Magnan’s culture imagery emphasizes the harsh realities of agrarian lifestyles; insular and mistrusting villages; hard and frugal villagers; historical continuity; and references to ruined or abandoned landscapes and cultural loss. Mayle’s sense of place defines Provence as a region defined as idyllic, most strongly developed by his culture imagery which emphasizes idealized agrarian lifeways and Provence’s food culture. This idyll is deepened with the positive associations with Provence’s tourist industry. Magnan’s sense of place defines Provence as a region defined by a melancholic sublime. His powerful, enigmatic nature imagery is the strongest shaping force behind developing Provence’s sublime qualities. Provence’s melancholic quality is linked to Magnan’s nature imagery’s enigmatic characteristics, which invite contemplation, and his culture imagery associated with ruins and cultural loss, which offers further invitation to contemplation and conveys a sense of grief.
Keywords: Literary geography; Sense of place; Regional imagery; Provence (France); Geography (0366)